2013
DOI: 10.1080/03650340.2012.709622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organic residues and mineral fertilizer application on soil–crop systems I: yield and nutrients content

Abstract: A five-season experiment was initiated to study the effects of the recycling of some organic residues on a soil-crop system of a guar-wheat rotation in a sandy clay loam soil located in the semi-arid tropics of Sudan. Treatments included: incorporation of crop residues alone after harvest (Cr þ ), with (FCr þ ) or without (FCr 7 ) inorganic fertilizer, sewage sludge (SS) and humentos (H). Grain yield of wheat in FCr þ and Cr þ treatments was significantly higher than that obtained in FCr 7 and control plots by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…Incorporation of crop residue with or without fertilizer and sewage sludge significantly changed soil physicochemical properties (Rezig et al 2013). The decomposition rate of wheat residue increased with the increase in N and P content in the soil.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Incorporation of crop residue with or without fertilizer and sewage sludge significantly changed soil physicochemical properties (Rezig et al 2013). The decomposition rate of wheat residue increased with the increase in N and P content in the soil.…”
Section: Discussionmentioning
confidence: 97%
“…and guar (Cyamopsis tetragonoloba local var.) in a crop rotation system (Rezig et al 2013). Treatments included recommended inorganic fertilizer 92 kg P 2 O 5 ha (271.7 kg urea ha -1 ) with crop residues (RF ?…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, abundant supply of chemical fertilizers in some countries has changed farmers' perception and appreciation of organic sources of nutrients such as manure (Schroder, 2005). It has also been reported that a combined input of both organic and chemical fertilizers have shown increased intensity and enhanced synchronization of nutrient release and uptake by crops causing improved yields (Mbah and Onweremadu, 2009;Kunzova, 2013;Rezig et al, 2013). Therefore, the challenge is to combine the right proportion and type of different qualities of organic nutrient inputs with chemical fertilizers to optimize nutrient availability to taro plants (Jate, 2012;Palm, 1997).…”
Section: Constraints In Organic Fertilizers Usagementioning
confidence: 99%
“…Nitrogen mineralisation proceeds more rapidly in residues rich in N and P, or in residues with a low C/N ratio (Abbasi et al, 2015;Nikolaidou et al, 2010). Generally, residues high in P, or with a low C/P ratio or N/P ratio, release more P within a shorter period (Baggie et al, 2004;Rezig et al, 2013;Vanzolini et al, 2017). Thus, high quality residues release nutrients rapidly, while nutrients from low quality residues are initially immobilised, and later are eventually mineralised and become available to crops (Herencia and Maqueda, 2016;Jensen et al, 2005;Xavier et al, 2013).…”
Section: Mulching For Soil Fertility Restoration In Smallholder Farmimentioning
confidence: 99%
“…Mulching with residues from multipurpose agro-forestry trees has also been proven to be a good source of nutrients to crops in the absence of mineral fertilisers (Bucagu et al, 2013). The tree residues serve mainly as natural resource options for supplying soil organic C and soil N, but also for other major nutrients through biological mineralisation, and this has resulted in increased crop yields (Mwango et al, 2016;Rezig et al, 2013;Shisanya et al, 2009). In coffee farming systems, the use of mulch of Tephrosia vogelii at 2.5 t of dry matter ha -1 in combination with NPK fertiliser and 1.41 t ha −1 resulted in a 33% increase in yield, from 2.1 t ha −1 to 2.8 t ha −1 (Bucagu et al, 2013).…”
Section: Mulching For Soil Fertility Restoration In Smallholder Farmimentioning
confidence: 99%